Oral administration of hydrolyzed collagen alleviates pain and enhances functionality in knee osteoarthritis: Results from a randomized, double-blind, placebo-controlled study - Juan Antonio Carrillo-Norte; Guillermo Gervasini-Rodríguez; María Ángeles Santiago-Triviño; Virginio García-López; Rafael Guerrero-Bonmatty (Contemporary Clinical Trials Communications)
Osteoarthritis (OA) is a major source of chronic pain and disability, representing a significant global health concern that affects 10–15 % of individuals aged over 60, with a higher prevalence among females than males. This investigation aimed to evaluate the impact of a dietary supplement containing collagen peptides (MW 1–3 kDa) on knee OA symptoms and inflammatory biomarkers such as C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR). Adults aged 30–81 years (50 % female) with grade II or III OA and a minimum pain score of 40 on the 0 to 100 visual analogue scale (VAS) were enrolled. Participants were randomly assigned to receive either 10 g of the test product (verum group) or placebo and were assessed at baseline (T0, pre-treatment) and after a six-month follow-up period (T6). Baseline characteristics were comparable between groups. At T6, the verum group exhibited significant reductions in VAS pain scores, Lequesne algofunctional index (LAI) scores, CRP levels (mg/L), and ESR (mm/h) compared to placebo (p < 0.001). No adverse effects were reported during the study, and the supplement demonstrated good tolerability and yielded satisfactory safety and acceptability. These findings suggest that the dietary supplement may serve as a complement to drug therapy for knee OA by alleviating osteoarticular pain, improving locomotor function and potentially reducing reliance on analgesic and anti-inflammatory medications. This study provides valuable insights into the efficacy and safety of collagen peptides in managing knee OA symptoms.